Postharvest needle retention in Norway spruce Christmas trees. Issue 8 (16th November 2020) - Pettersson, Martin; Talgø, Venche; Johnskås, Odd Ragnar; Skage, Jan-Ole; Torp, Torfinn; Fløistad, Inger Sundheim
ABSTRACT: Norway spruce ( Picea abies ) is a widely used Christmas tree species in the Nordic countries. Postharvest needle retention is an important characteristic for Christmas trees and compared to many fir ( Abies ) species, Norway spruce has poor postharvest needle retention. This trait is one of the most important qualities in choice of natural versus plastic trees. In this study, current year shoots were cut from 30 Norway spruce seedlot sources, including the most widely used Norwegian Christmas tree provenances, and tested to identify genetic variation in postharvest needle retention. Current year shoots were collected from one field in November and December 2018, and from three fields in October, November and December 2019. The current year shoots were displayed indoors under controlled conditions and allowed to dry. Differences in postharvest needle retention were seen between seedlots, harvesting dates and locations. Our study indicates possibilities of selecting for improved postharvest needle retention in Norway spruce seed sources. Furthermore, postharvest needle retention should be considered as one characteristic to add in the ongoing Norway spruce Christmas tree breeding program.